Model of Conservation on Sagara Anakan Environment - Sugandi, Dede (Forum Geografi, 2013)
Widespread decline in agricultural land and the impact on production decline caused extensive forest activities to meet the needs of the population. Activities that cause less environmental quality offset environmental balance changes. These changes due to deforestation, erosion, degraded land and natural resource degradation are exploited so that the function of ecological, economic and social life. Damaged ecosystems resulting in erosion, landslides in the watershed affect the sedimentation in Sagara Anakan sea. Silting, resulting in narrowing of fishing activities, tourism, sports, and services decreased crossings. Because of the problem and the purpose of this study proposed and analyzed a few questions: 1) How does the socio-economic impact of farmers in conserving the environment of Sagara Anakan ?, 2) How do people form of conservation and coastal of Sagara Anakan ?, 3) How model of integrated conservation in the watershed and coastal of Sagara Anakan ? and 4) What role do the people in the watershed and coastal on Sagara Anakan conservation ?. Study site covers an area of flow and Ci Ci Tanduy Beureum and Sagara Tillers waters. Activities of the population in the process of land affected when in Sagara tillers. The method used was a survey with a sample divided by the watershed upstream, downstream and coastal tengahm. Using statistical analysis techniques and geography, so that part of the watershed characteristics can be imaged. Shallowing Sagara Anakan, physically was affected by the physical condition of the easily eroded and accelerated by human activities. The activities of farmer on the watershed have done conservation unless doing reforestation, whereas the farmer on the swamp and coastal areas are not doing conservation. Different physical circumstances, the conservation of watersheds and coastal forms differ. Socio-economic condition of farmer affect the conservation. The farmer could not reforestation conservation form, as the socio-economic needs. While in the farmer swamp and coastal conservation is not done, because the physical state was not possible. To conserve of Sagara Anakan, then the shape of coastal conservation by planting trees, not catch fish, marine dredging, not taking out the trash, do not use drugs to win the fish and catch a certain size. While in conservation should be done with different shape and performed in an integrated manner that requires the participation of the population.